2001
DOI: 10.1103/physrevd.64.045010
|View full text |Cite
|
Sign up to set email alerts
|

Quantum fluctuations of radiation pressure

Abstract: Quantum fluctuations of electromagnetic radiation pressure are discussed. We use an approach based on the quantum stress tensor to calculate the fluctuations in velocity and position of a mirror subjected to electromagnetic radiation. Our approach reveals that radiation pressure fluctuations are due to a cross term between vacuum and state dependent terms in a stress tensor operator product. Thus observation of these fluctuations would entail experimental confirmation of this cross term. We first analyze the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 11 publications
0
71
1
1
Order By: Relevance
“…For the case of light in a coherent state, this effect was first analyzed by Caves [18,19], using an approach based upon fluctuation in photon numbers. It was studied by the present authors [20] using the quantum stress tensor, where it was shown that the radiation pressure fluctuations arise entirely from the cross term in the correlation function. This follows from the fact that for a single mode coherent state |z ,…”
Section: Fluctuations Of Forces On Materials Bodiesmentioning
confidence: 99%
“…For the case of light in a coherent state, this effect was first analyzed by Caves [18,19], using an approach based upon fluctuation in photon numbers. It was studied by the present authors [20] using the quantum stress tensor, where it was shown that the radiation pressure fluctuations arise entirely from the cross term in the correlation function. This follows from the fact that for a single mode coherent state |z ,…”
Section: Fluctuations Of Forces On Materials Bodiesmentioning
confidence: 99%
“…Quantum stress tensor fluctuations can have a variety of physical effects, and have been discussed by several authors [14][15][16][17][18][19][20][21][22][23][24][25][26]. These effects include radiation pressure fluctuations [14], and passive quantum fluctuations of gravity, where the gravitational field fluctuates in response to matter stress tensor fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…These effects include radiation pressure fluctuations [14], and passive quantum fluctuations of gravity, where the gravitational field fluctuates in response to matter stress tensor fluctuations. Much of the previous work on this topic has involved calculating mean squared effects using integrals of a stress tensor correlation function.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum fluctuations of the stress tensor operator have been studied in numerous recent papers [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. Fluctuations of the stress tensor drive passive fluctuations of the gravitational field, which are to be distinguished from the active fluctuations due to the quantization of the gravitational degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%